Computational Biomechanics for Medicine Measurements, Models, and Predictions - Nielsen, Poul M. F.; Wittek, Adam; Miller, Karol; Doyle, Barry; Joldes, Grand R.; Nash, Martyn P. (Springer International Publishing : Imprint: Springer, 2019)
This volume comprises the latest developments in both fundamental science and patient-specific applications, discussing topics such as: cellular mechanics, injury biomechanics, biomechanics of the heart and vascular system, algorithms of computational biomechanics for medical image analysis, and both patient-specific fluid dynamics and solid mechanics simulations. With contributions from researchers world-wide, Computational Biomechanics for Medicine: Measurments, Models, and Predictions provides an opportunity for specialists in the field to present their latest methodologies and advancements.